Wywiad i obserwacje lekcji w badaniach nad osobą nauczyciela języków obcych - Wysocka, Maria (Neofilolog, 2019)
The paper presents the value of qualitative studies on the person of the FL teacher since s/he is the one who organizes the whole teaching-learning process and takes the whole responsibility for it. It is of crucial importance, therefore, to collect from teachers as much data as possible by means of which our knowledge about the quality of the whole process could be described, discussed and improved in the best way. Interviews and all types of lesson observations are presented here as the optimal tools to achieve this aim.